2017
DOI: 10.1002/ptr.5807
|View full text |Cite
|
Sign up to set email alerts
|

Epimedii Herba: A Promising Herbal Medicine for Neuroplasticity

Abstract: Epimedii Herba (EH) is an herbal medicine originating from several plants of the genus Epimedium. It is a major therapeutic option for kidney yang deficiency syndrome, which is closely related to androgen hormones and also has been used to treat hemiplegia following a stroke in traditional medicine of Korea and PR China. To date, many clinical and basic researches of EH have shown the activities on functional recovery from brain diseases. Recently, neuroplasticity, which is the spontaneous reaction of the brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 94 publications
0
19
0
Order By: Relevance
“…Epimedii Herba is an herbal medicine originating from several plants of the genus Epimedium . It is a major therapeutic option for kidney Yang deficiency syndrome, which is closely related to androgen hormones ( Cho et al, 2017 ). Icariin, as the main hydrophilic ingredient of Epimedium brevicornu Maxim, has been proven to be a plant sex hormone Liu et al (2021) , and has testosterone mimetic properties ( Zhang and Yang, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Epimedii Herba is an herbal medicine originating from several plants of the genus Epimedium . It is a major therapeutic option for kidney Yang deficiency syndrome, which is closely related to androgen hormones ( Cho et al, 2017 ). Icariin, as the main hydrophilic ingredient of Epimedium brevicornu Maxim, has been proven to be a plant sex hormone Liu et al (2021) , and has testosterone mimetic properties ( Zhang and Yang, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we published a review paper detailing the effects of EH on brain diseases and concluded that the protective functional effects of EH on those diseases might be largely a result of neuroplasticity [15]. Recently, icariin was reported to improve cognitive impairment in closed head injury via enhanced hippocampal cholinergic function [16].…”
Section: Icariin Improves Functional Behavior In a Mouse Model Of Tramentioning
confidence: 99%
“…Epimedii Herba (Chinese name: Yinyanghuo), consisting of the dried leaves of several Epimedium plants [16], has been widely utilized in the clinic for the treatment of a variety of disorders, such as erectile dysfunction, seminal emission, chronic musculoskeletal pain, infertility, urinary frequency, urinary incontinence, chronic impediment diseases, hypertension, hemiplegia following a stroke, polio, coronary sclerosis, angina pectoris, palpitation, chronic bronchitis, and leukopenia [17]. This precious HM is also able to improve the life-quality of patients undergoing maintenance hemodialysis [18].…”
Section: Introductionmentioning
confidence: 99%